Toxic elements in the с 1 coal seam of the blahodatna mine of pavlohrad-petropavlivka geological and industrial area of Donbas - Kozii, Ye.S. (ІГТМ НАН України, 2021)
The features of the distribution of toxic elements in the c 1 coal seam of «Blahodatna» mine field are considered. The research aims to establish regularities in the distribution of toxic elements in the coal seam c 1 of Blahodatna mine of Pavlohrad-Petropavlivka geological and industrial area of Donbas. Samples were taken from mine opening (reservoir samples, selected by the trench method and from duplicates of drill core personally). Content of toxic elements was determined by quantitative emissive spectrum analysis. The values of the main descriptive statistical indicators were calculated..

У статті розглянуто особливості розподілу потенційно токсичних елементів у вугіллі пласта с 1 шахти «Благодатна». Мета роботи - встановити закономірності в розподілі потенційно токсичних елементів у вугіллі пласта с 1 поля шахти «Благодатна» Павлоградсько-Петропавлівського геолого-промислового району Донбасу.

В статье рассмотрены особенности распределения потенциально токсичных элементов в угле пласта шахты «Благодатная». Цель работы – установить закономерности в распределении потенциально токсичных элементов в угле пласта с 1 поля шахты «Благодатная» Павлоградско-Петропавловского геолого-промышленного района Донбасса.
Токсичні елементи у вугіллі пласта с 1 шахти «благодатна» Павлоградсько-Петропавлівського геолого-промислового району Донбасу
Keywords: toxic and potentially toxic elements; thickness of a coal seam; ash content; content of total sulfur; map of isoconcentrate; map of the regional constituent of content; linear regression equation; потенційно токсичні елементи; вугільний пласт; карта ізоконцентрат; карти регіональної складової; лінійні рівняння регресії; потенциально токсичные элементы; угольный пласт; карта изоконцентрат; карты региональной составляющей; линейные уравнения регрессии